Menneskets forståelse af sig selv mellem dyret og det guddommelige - Karlsen, Mads Peter (Dansk teologisk tidsskrift, 2023)
This review article presents an outline and discussion of Lars Albinus’ monograph Livsvæsen. Om forholdet mellem dyret, mennesket og det guddommelige (‘A Living Being. On the Relationship between Animals, Human Beings and the Divine’). Focusing on the book’s guiding question concerning the issue of human self-understanding in relation to the animal and the divine, the aim of the article is to explore its relevance for contemporary philosophy of religion. The first part of the article sketches how Albinus, through a reading of philosophers like Heidegger, Agamben and Derrida, elaborates the complex and ambiguous part the animal plays in the attempt of human beings to understand themselves. The second part discusses Albinus’ two main analytical perspectives - philosophy of religion and history of religions - and their compatibility, using Albinus’ key-concept of the animal-human-divine triad as the pivotal point. The third and last section of the review article initiates a critical discussion of some of the implications and possibilities of Albinus’ guiding question concerning human self-understanding.